2017
DOI: 10.15453/2168-6408.1258
|View full text |Cite
|
Sign up to set email alerts
|

A Service Delivery Model for Addressing Activity and Social Participation Needs of People Living with HIV

Abstract: Background: Occupational therapy can contribute to the health and well-being of people with human immunodeficiency virus (HIV) who are experiencing health consequences of living long term with this disease. However, there are no comprehensive rehabilitation service delivery models to guide this emerging area of practice. The purpose of this study was to obtain critical feedback about a service delivery model to address the activity and social participation needs of people living with HIV. Method: We developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…In seven studies, individuals with experience of living with mental illness, or service user experience within mental health were the public collaborators ( Baker & Procter, 2014 ; Birken & Bryant, 2017, 2019; Bryant et al, 2016 ; Hancock et al, 2015 ; Makdisi et al, 2013 ; Williamson & Ennals, 2020 ). Other public collaborators included older adults ( Andonian & MacRae, 2011 ), residents in prison ( Crabtree, Ohm, et al, 2016 ), or persons living with chronic conditions ( Nielsen et al, 2019 ; Restall et al, 2017 ). Public collaborators did not always have patient experience relevant to the study.…”
Section: How Ppi Was Carried Outmentioning
confidence: 99%
See 3 more Smart Citations
“…In seven studies, individuals with experience of living with mental illness, or service user experience within mental health were the public collaborators ( Baker & Procter, 2014 ; Birken & Bryant, 2017, 2019; Bryant et al, 2016 ; Hancock et al, 2015 ; Makdisi et al, 2013 ; Williamson & Ennals, 2020 ). Other public collaborators included older adults ( Andonian & MacRae, 2011 ), residents in prison ( Crabtree, Ohm, et al, 2016 ), or persons living with chronic conditions ( Nielsen et al, 2019 ; Restall et al, 2017 ). Public collaborators did not always have patient experience relevant to the study.…”
Section: How Ppi Was Carried Outmentioning
confidence: 99%
“…PPI was also reported with respect to involvement in the data collection strategy ( Bryant et al, 2016 ; Makdisi et al, 2013 ): by including public collaborators in interviewer team ( Birken & Harper, 2017 ; Crabtree, Ohm, et al, 2016 ; Hancock et al, 2015 ) or in the collection of data ( Birken & Bryant, 2019 ; Turcotte et al, 2019 ). Involvement in data analysis was reported as, for example, involving public collaborators in interpreting the findings ( Birken & Harper, 2017 ), reviewing the coding scheme ( Restall et al, 2017 ), identifying categories ( Andonian & MacRae, 2011 ; Crabtree, Ohm, et al, 2016 ), and regular discussions during data analysis ( Bryant et al, 2016 ; Makdisi et al, 2013 ). Involvement in dissemination of results included help to formulate recommendations ( Ball & Shanks, 2012 ), involvement in education session ( Ripat et al, 2010 ) or simply as “public collaborators were involved in the dissemination” ( Simpson et al, 2020 ; Turcotte et al, 2019 ), without further descriptions.…”
Section: How Ppi Was Carried Outmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings provide valuable insights for enhancing the accessibility, empathy, and responsiveness of financial aid services at a university, ultimately contributing to a more inclusive and supportive environment for all students. The study's recommendations offer a pathway for addressing the identified challenges and improving the overall quality of service delivery within the Department, aligning with the broader literature on service quality and delivery in various contexts (Entwistle et al, 2012;Hartanti et al, 2022;Restall et al, 2017).…”
Section: Discussionmentioning
confidence: 94%